The Role Of Female Vegetable Vendors In Contributing To Household Income At The Main Market Of Wonomulyo Sub-District - Rahim, Farida; Asrandi , Asrandi; Suhab, Resky Faradibah (Jurnal Economic Resource, 2025)
This study aims to examine and analyze the role of female vegetable vendors in increasing household income at the Main Market of Wonomulyo Sub-district, Polewali Mandar Regency. The research is based on the socio-economic reality of lower-middle-class households, where women not only fulfill domestic roles but also actively participate in income-generating activities. A qualitative descriptive approach was employed, with data collected through in-depth interviews with ten purposively selected informants. Findings indicate that the primary motivation for women to engage in vegetable trading is to support family needs due to unstable husband incomes. The average daily income of the informants was IDR 121,000, with contributions to household income ranging from moderate (30%–60%) to high (>60%). Supporting factors include the number of dependents, access to business capital, and the habit of saving as a form of financial management. These results demonstrate that female vegetable vendors play a strategic role in sustaining household economies and contribute significantly to economic resilience. Therefore, their contributions deserve recognition and support through access to capital, entrepreneurship training, and adequate social protection.